EFFECTIVENESS TEST OF ANTI-BACTERIAL LIME JUICE (Citrus aurantifolia) ON SALMONELLA SP BACTERIA IN SALMON FISH (Oncorhynchus nerka) - Qori Fadillah; Linda Chiuman; Chrismis Novalinda Ginting; Ermi Girsang (Universitas Medan Area, 2020)
Salmonella Sp is a gram-negative pathogens that are often found in marine foods,one of process of serving salmon is channeling lime juice, where lime juice is acidic and has phytochemical properties that have anti-bacterial properties. This study aims to explore anti-bacterial effect lime juice on Salmonella thypii bacteria in Salmon. This research is an experimental study using disc diffusion method. Lime samples that were used were purchased from one of the modern markets in Medan which were made in several series of concentrations using distilled water as a solvent, while the salmon samples used in this study were purchased from one of the Japanese dining restaurants located in Medan City. Meanwhile, isolation of Salmonella thypii bacteria from salmon samples was carried out using nutrient broth and SSA media. The results of this study indicate that differences in concentration indicate the differences in the diameter of the inhibitory zone (P value = 0.000). With the diameter of the widest inhibition zone formed by a concentration of 100% is 15.40 ± 0.44 mm and the smallest diameter is formed by a concentration of 5% which is 7.23 ± 0.55 mm. Thus, it can be concluded that the lime juice has anti-bacterial activity against Salmonella thypii bacteria from salmon.